2011
DOI: 10.1523/jneurosci.2156-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus with a Normal Audiogram: Physiological Evidence for Hidden Hearing Loss and Computational Model

Abstract: Ever since Pliny the Elder coined the term tinnitus, the perception of sound in the absence of an external sound source has remained enigmatic. Traditional theories assume that tinnitus is triggered by cochlear damage, but many tinnitus patients present with a normal audiogram, i.e., with no direct signs of cochlear damage. Here, we report that in human subjects with tinnitus and a normal audiogram, auditory brainstem responses show a significantly reduced amplitude of the wave I potential (generated by primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
834
13
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 837 publications
(952 citation statements)
references
References 37 publications
45
834
13
12
Order By: Relevance
“…They are in agreement with previous reports of the following in tinnitus subjects: elevated V/I amplitude ratio (Kehrle et al 2008;Schaette and McAlpine 2011), elevated wave III amplitude (Attias et al 1996), and reduced wave I amplitude (Attias et al 1993;Schaette and McAlpine 2011). An absence of reduction in wave III of tinnitus subjects (Attias et al 1993) or wave V (Attias et al 1993; Schaette and McAlpine 2011), despite reduced wave I, has also been reported, which is tantamount to enhanced activity given the reduction in wave I (as discussed above).…”
Section: Comparison To Previous Abr Studies Of Tinnitussupporting
confidence: 93%
See 2 more Smart Citations
“…They are in agreement with previous reports of the following in tinnitus subjects: elevated V/I amplitude ratio (Kehrle et al 2008;Schaette and McAlpine 2011), elevated wave III amplitude (Attias et al 1996), and reduced wave I amplitude (Attias et al 1993;Schaette and McAlpine 2011). An absence of reduction in wave III of tinnitus subjects (Attias et al 1993) or wave V (Attias et al 1993; Schaette and McAlpine 2011), despite reduced wave I, has also been reported, which is tantamount to enhanced activity given the reduction in wave I (as discussed above).…”
Section: Comparison To Previous Abr Studies Of Tinnitussupporting
confidence: 93%
“…Kehrle et al (2008), comparing tinnitus and non-tinnitus subjects with clinically normal thresholds, reported an enhanced V/I amplitude ratio in tinnitus subjects. While they did not report whether the enhanced amplitude ratio arose from a reduction in wave I, an elevation in wave V or, a combination of both, the earlier data of Attias et al (1993) and recent report of Schaette and McAlpine (2011) indicate that reduced wave I was a factor. Although the study of Barnea et al (1990) reported normal ABR amplitudes in tinnitus subjects with clinically normal audiograms, it compared the tinnitus data with clinical norms, not with a closely matched control group, an approach suitable for detecting gross ABR abnormalities but not subtler ones.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The majority of respondents reported some degree of hearing loss (494, 76.8%), consistent with the association between tinnitus and hearing loss [15]; [16]. The largest group of respondents reported mild hearing loss (n=261, 40.6%), with 149 respondents reporting no hearing loss (23.2%), 172 -moderate (26.8%) and 61 severe/profound hearing loss (9.5%).…”
Section: Figure 2 Age Distribution For All Respondents (Black Bars)supporting
confidence: 63%
“…Nevertheless, increases in ABR amplitude, assumed to be triggered by deafferentation, have been reported elsewhere (e.g. Schaette and McAlpine 2011;Gu et al 2012).…”
Section: Mechanisms Mediating Rapid Reduction In Abr Latency Post-udmentioning
confidence: 76%